KEDAULATAN POPULER DI TENGAH KEDAULATAN NEGARA, YURIDIKSI DOMESTIK, DAN INTERVENSI - Zein, Patra M (UI Scholars Hub, 2004)
Under the theme of state's sovereignty, this article puts intervention as its main framework, from the use of traditional threats, i.e. the threat of physical power and state's illegal actions, to the indirect threats which are contained by international trade's unfair conduct. Using international law perspective as its background, this article describes the